2007
DOI: 10.2353/ajpath.2007.070066
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Growth Factor Synergism in a Murine Tissue Engineering Model of Angiogenesis and Adipogenesis

Abstract: De novo tissue generation stimulated by three angiogenic growth factors administered in a factorial design was studied in an in vivo murine tissue engineering chamber. A silicone chamber was implanted around the epigastric pedicle and filled with Matrigel with 100 ng/ml of recombinant mouse vascular endothelial growth factor-120 (VEGF 120 ), recombinant human basic fibroblastic growth factor (FGF-2), or recombinant rat platelet-derived growth factor-BB (PDGF-BB) added as single, double, or triple combinations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 34 publications
(39 reference statements)
6
77
1
Order By: Relevance
“…Indeed, in some previous reports, superior results for angiogenesis have been obtained through the application of multiple factors than through the introduction of a single factor, eg, paired combinations of bFGF and PDGF, 26,27 VEGF and bFGF, 28,29 VEGF and PDGF, 30 or PDGF and TGF-␤, 31 or a triple combination of bFGF, PDGF, and VEGF. 32 Our findings with incomplete AIC with either two or three growth factors suggest that PDGF, EGF, and TGF-␤ contributed to hASC migration and that bFGF played a pivotal role in network formation, although these effects were likely augmented by the synergism of all of the factors. Although the reproducible methods for inducing hASC Wholemount histologic analysis of living adipose tissue.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, in some previous reports, superior results for angiogenesis have been obtained through the application of multiple factors than through the introduction of a single factor, eg, paired combinations of bFGF and PDGF, 26,27 VEGF and bFGF, 28,29 VEGF and PDGF, 30 or PDGF and TGF-␤, 31 or a triple combination of bFGF, PDGF, and VEGF. 32 Our findings with incomplete AIC with either two or three growth factors suggest that PDGF, EGF, and TGF-␤ contributed to hASC migration and that bFGF played a pivotal role in network formation, although these effects were likely augmented by the synergism of all of the factors. Although the reproducible methods for inducing hASC Wholemount histologic analysis of living adipose tissue.…”
Section: Discussionmentioning
confidence: 88%
“…FGF-2 has enjoyed significant popularity as a potential regulator for adipose formation when Matrigel is implanted in small animal models [3,17]. The levels of FGF-1 and FGF-2 in the extracts were quantified using sandwich ELISAs.…”
Section: Sandwich Fgf-1 and Fgf-2 Elisasmentioning
confidence: 99%
“…Rophael et al investigated the effects of angiogenic growth factors including vascular endothelial growth factor, FGF-2 and platelet derived growth factor-BB in an in vivo murine model in which implanted chambers were filled with growth factor-reduced MatrigelÔ supplemented with growth factor combinations. The study indicated that MatrigelÔ with angiogenic growth factors promoted neovascularization and adipose tissue formation [17]. Studies have also shown that supplementation of MatrigelÔ with an adipose graft promotes rapid adipogenesis by host cells [15].…”
Section: Introductionmentioning
confidence: 97%
“…Rophael et al, found the cocktail of angiogenic growth factors (VEGF, FGF, PDGF-BB) does not only enhance early angiogenesis, but also late de novo adipogenesis compared to each single growth factor in a murine tissue engineering model. 45 Hence, the angiogenic effect of PRP might not only maintain the survival of mature fat cells, but also induce de novo adipogenesis.…”
Section: Specific Role Of Growth Factors In Prpmentioning
confidence: 99%